(untitled) (Conferencea, 2022)
This article discusses the historisms in the Uzbek dictionary. Teaching Uzbek in this article use as a lecture in the process of learning the language of archaic forms communicate to students how important it is, a compiled dictionary of archaisms and obsolete words. The results of the article can be used to teach the lexicography department of Uzbek linguistics.